The Oxford handbook of the Books of Kings - McKenzie, Steven L.; Richelle, Matthieu (Oxford handbooks online Religion, 2024)
The Books of Kings have long been at the centre of scholarly discussions on the Hebrew Bible because they constitute important sources for the history of ancient Israel and Judah, and because they are key components of the Deuteronomistic History. 'The Oxford Handbook of the Books of Kings' provides a clear and useful introduction to the main aspects and issues pertaining to the scholarly study of Kings. These include textual history (including the linguistic profile), compositional history, literary approaches, key characters, history, important recurring themes, reception history and some contemporary readings. As a one-volume introduction embracing all the aspects of the study of Kings, written by an international and diverse team of scholars, this handbook is the ideal point of entry into the study of Kings for generations of students and scholars.